How Culture Influeneces Consumer Loyalty towards Cosmetic Products. A comparision of UK and Taiwanese Consumers - Chen, Hsin-Ping (2007)
Abstract Culture is one of the most important factors affecting the marketing department to shape their strategy. This is particularly true when facing global marketing. This project is aimed at examining how the culture influences brand loyalty towards cosmetic products by comparing consumer behaviours of UK and Taiwanese consumers. Semi-structured interviews are conducted in order to collect data. By applying a qualitative approach, this project provides an insight of the cultural factors influencing consumer behaviour. Furthermore, some managerial implication and directions of further research are presented in this project.